Investigation of silica nanoparticles by Auger electron spectroscopy (AES)1. (16th January 2014) - Rades, S.; Wirth, T.; Unger, W.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> High‐priority industrial nanomaterials like SiO2, TiO2, and Ag are being characterized on a systematic basis within the framework of the EU FP7 research project NanoValid. Silica nanoparticles from an industrial source have been analyzed by Auger electron spectroscopy. Point, line, and map spectra were collected. Material specific and methodological aspects causing the special course of Auger line scan signals will be discussed. Copyright © 2014 John Wiley & Sons, Ltd.